It's a Small(er) World: The Role of Geography and Networks in Biotechnology Innovation - Daniel K.N. Johnson; Milena Mareva (Wellesley College, Department of Economics, 2002)
Using patent citation data for the U.S., we test whether knowledge spillovers in biotechnology are sensitive to distance. Controlling for self-citation by inventor, assignee and examiner, cohort-based regression analysis shows that spillovers are local but that distance is becoming less important with time. Network analysis paints a picture of a stable network between states, but a changing environment between individual actors, with a growing importance of connectedness. The popular maxim that everyone is connected by six degrees of separation is tested with surprising results.
Keywords: N9; O3; R1; L6; 330; Biotechnische Industrie; Innovation; Patent; Spillover-Effekt; Wissenstransfer; Regionale Konzentration; Schätzung; USA